2007
DOI: 10.1177/0265407507079235
|View full text |Cite
|
Sign up to set email alerts
|

Love at first sight or friends first? Ties among partner personality trait similarity, relationship onset, relationship quality, and love

Abstract: The present study examined the relation between the type of relationship onset on the one hand and the degree to which partners have similar personalities and relationship quality on the other hand. It was hypothesized that partners who fell in love at first sight, relative to partners who got involved more gradually, entered into intimate relationships more shortly after they met, would have mates with less similar personalities, especially with regard to levels of extraversion, emotional stability and autono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 42 publications
7
51
1
1
Order By: Relevance
“…For individuals who seek a mate for a long-term, harmonious relationship, finding a similar mate is therefore important, or at least, should be. In general, however, partners have been found to have only somewhat similar personalities (e.g., Barelds & Dijkstra, 2007;Botwin et al, 1997;Dijkstra & Barelds, 2008;McCrae et al, 2008;Rammstedt & Schupp, 2008). Several explanations have been forwarded for this discrepancy.…”
Section: In Thementioning
confidence: 99%
See 4 more Smart Citations
“…For individuals who seek a mate for a long-term, harmonious relationship, finding a similar mate is therefore important, or at least, should be. In general, however, partners have been found to have only somewhat similar personalities (e.g., Barelds & Dijkstra, 2007;Botwin et al, 1997;Dijkstra & Barelds, 2008;McCrae et al, 2008;Rammstedt & Schupp, 2008). Several explanations have been forwarded for this discrepancy.…”
Section: In Thementioning
confidence: 99%
“…Several explanations have been forwarded for this discrepancy. For instance, Barelds and Dijkstra (2007) argue that individuals usually do not take the time to get to know each other properly before they get romantically involved. Indeed, these authors showed that individuals who took the time to get to know each other's personalities and became friends before they got romantically involved -in contrast to those who became romantically involved relatively quickly -ended up with a partner with a more similar personality.…”
Section: In Thementioning
confidence: 99%
See 3 more Smart Citations